The Developmental Neurotoxicity of Arsenic: Cognitive and Behavioral Consequences of Early Life Exposure - Molly Tolins; Mathuros Ruchirawat; Philip Landrigan (Ubiquity Press, 2014)
Background: More than 200 million people worldwide are chronically exposed to arsenic. Arsenic is a known human carcinogen, and its carcinogenic and systemic toxicity have been extensively studied. By contrast, the developmental neurotoxicity of arsenic has been less well described. The aim of this review was to provide a comprehensive review of the developmental neurotoxicity of arsenic. Methods: We reviewed the published epidemiological and toxicological literature on the developmental neurotoxicity of arsenic. Results: Arsenic is able to gain access to the developing brain and cause neurotoxic effects. Animal models link prenatal and early postnatal exposure to reduction in brain weight, reductions in numbers of glia and neurons, and alterations in neurotransmitter systems. Animal and in vitro studies both suggest that oxidative stress may be a mechanism of arsenic neurotoxicity. Fifteen epidemiological studies indicate that early life exposure is associated with deficits in intelligence and memory. These effects may occur at levels of exposure below current safety guidelines, and some neurocognitive consequences may become manifest only later in life. Sex, concomitant exposures, and timing of exposure appear to modify the developmental neurotoxicity of arsenic. Four epidemiological studies failed to show behavioral outcomes of arsenic exposure. Conclusions: The published literature indicates that arsenic is a human developmental neurotoxicant. Ongoing and future prospective birth cohort studies will allow more precise definition of the developmental consequences of arsenic exposure in early life.